Local stakeholders participation in developing sustainable community based rural tourism (CBRT): The case of three villages in the East Coast of Malaysia - Kamarudin, Khairul Hisyam (2013)
This paper firstly, discusses the concept of stakeholders participation in developing sustainable community based rural tourism (CBRT) with respect to types of community participation, strengths, motivations and barriers to participation in sustainable CBRT. Secondly, a discussion on the survey of local stakeholders via questionnaires, which were, carried out in three CBRT sites in the East Coast of Malaysia. This survey was conducted to identify main reasons for local participation in CBRT, followed by an analysis of likelihood of local stakeholders to be included in sustainable CBRT’s decision-making process. 78% of the respondents (a total of 85) indicated that the likelihood of them being included in decision-making process has improved. The paper also indicated two major influential factors for greater participation of local stakeholders in the decision-making process i.e. good and workable CBRT organisations and presence of strong leadership. This paper concludes by commenting on the proposed process to enhance participation of local stakeholders in developing and sustaining sustainable CBRT.